Nghiên cứu về giáo dục chính trị cho sinh viên đại học ở Việt Nam: Tổng quan các hướng tiếp cận, khoảng trống và định hướng nghiên cứu - Nguyễn Thị Kim Oanh, Nguyễn Thị Kim Oanh (Tạp chí Giáo dục, 2026)
Political education plays a crucial role in shaping political awareness, moral values, and civic responsibility among university students as future intellectuals. In the context of digital transformation and the pervasive influence of social media, political education in higher education faces increasing demands for innovation. This article conducts a structured thematic literature review of Vietnamese studies on political education for university students published between 2017 and 2025. The findings indicate that existing research primarily addresses educational content, forms, roles, current practices, influencing factors, and proposed solutions for improving quality. However, the literature remains fragmented, with limited systematic synthesis and insufficient evidence on long-term effectiveness. Based on these findings, the article suggests several future research directions to support the renewal of political education for university students in contemporary contexts.